GAMBARAN FAKTOR RISIKO GLAUKOMA PRIMER PADA LANSIA DI RSUP DR. M. DJAMIL PADANG TAHUN 2017-2019 - Efriza Efriza; Zukhri Zainun; Rio Inaldo (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Glaucoma is one of the main causes of decreased vision and blindness in the elderly, so it can increase the morbidity of the elderly. The risk factors for glaucoma in the elderly can be the elderly and family history. Objective: To describe the risk factors for primary glaucoma in the elderly at Dr. M. Djamil Padang. Methods: This type of research design is descriptive observational with a retrospective research design. The population of this study was all elderly patients who had been diagnosed by doctors suffering from primary glaucoma at RSUP Dr. M. Djamil Padang from January 2017 to December 2019 with 52 samples using a simple random sampling technique. The measuring instrument used medical record data and analyzed using a univariate test and presented in the form of a frequency distribution table and percentage. Result: The study results showed that the elderly who suffered from glaucoma mainly were between 60-74 years old (elderly), namely 82.7%, and the male sex was 67.3%. The most common type of glaucoma suffered by the elderly was open- angle glaucoma, which was 82.7%. Elderly who experience myopia by 57.7%, who have diabetes by 9.6% and who have hypertension by 36.5%, and who have a family history of glaucoma sufferers by 3.8%. Conclusion: Elderly with primary glaucoma at Dr. RSUP. M. Djamil Padang in 2017-2019 at most 60 – 74 years (elderly) and the most are male. The most common type of glaucoma that affects the elderly is primary open-angle glaucoma (POAG) with indications of myopia, DM, hypertension, and family history.